Project Strories Book Terhadap Bahasa Ekspresif Anak Usia 5-6 Tahun di TK Al Hijrah Kampung Beru - Khatimah, Ummul; Amri, Nur Alim; Latief, Fadhilah (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
Project Stories Book is an effective learning method to improve children's language skills. By creating a project stories book, children can directly practice activities carried out at home. Expressive language skills are one of the important aspects that must be developed in the early childhood language learning process. This study aims to analyze the effect of project stories book on the expressive language of children aged 5-6 years in group B of Al Hijrah Kindergarten, Kampung Beru, Galesong District, Takalar Regency. This type of research is an experiment that aims to determine expressive language skills with project stories book. The study population was 42 students of Al Hijrah Kindergarten, Kampung Beru Group B. The research sample was determined by purposive sampling, namely 22 students from group B. Data sources used in this study include observation, documentation, and interviews. Data analysis used the Wilcoxon signed rank test using the SPSS 26 application. The results showed that there were 3 children who showed adequate expressive language skills, while 19 other children still experienced problems in expressive language. One of the problems that often arises among the 19 students is a lack of concentration during the learning process.